‘Where all my bad girls at?’: cosmopolitan femininity through racialised appropriations in K-pop - Garza, Joyhanna Yoo (Gender and Language, 2021)
This article examines the polyvalence of racial(ised) representations in K-pop performances. The analysis of K-pop star CL’s (2013) song and video ‘Nappeun gijibae’ (‘The bad girl’) demonstrates how the artist projects an assertive femininity by embodying and localising the Bad Bitch: a sexually agentive figure of womanhood from US hip hop. CL’s use of African American English and conventionalised hip hop tropes helps resignify gijibae, a pejorative Korean term for women. By shifting between decontextualised styles invoking a different time and place, CL is able to build a kind of chronotopic capital that transforms fragmented styles into an empowered cosmopolitan femininity. However, although CL’s performance challenges Korean gendered norms in its use of local linguistic resources, her selective appropriations of US Black and Chicanx cultural signifiers reproduce narrow images of racialised femininities and reify a hierarchy of valuation along lines of gender and race.
Keywords: 2000 à aujourd'hui; K-pop; approches et analyses; appropriation culturelle; asie; chronotope; corps; corée du sud; cours; discipline; féminisme pop; lin2685; linguistique; performance de genre; premier cycle; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques

Rethinking the effects paradigm in porn studies - McNair, Brian (Porn Studies, 2014)
It has been an assumption of most anti-pornography discourse that porn damages women (and children) in a variety of ways. In Porno? Chic!, the author interrogated this assumption by examining the correlation between the incidence of sexual violence and other indicators of misogyny, and the availability and accessibility of pornography within a number of societies. This article develops that work with a specific focus on the regulatory environment as it relates to pornography and sexual representation. Does a liberal regulatory regime in sexual culture correlate with a relatively advanced state of sexual politics in a given country? Conversely, does an illiberal regime, where pornography and other forms of sexual culture are banned or severely restricted, correlate with relatively strong patriarchal structures? A comparative cross-country analysis seeks to explain the correlations identified, and to assess the extent to which the availability of porn can be viewed as a causal or a consequential characteristic of those societies where feminism has achieved significant advances.
Keywords: LGBTQIA2+; analyse comparée; approches et analyses; communication; corps; cours; discipline; droits des femmes*; féminisme pop; histoire et politique; identités LGBTQIA2+; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; violences; études culturelles

The feminist porn book: the politics of producing pleasure - Taormino, Tristan; Shimizu, Celine Parreñas; Penley, Constance; Miller-Young, Mireille (The Feminist Press at the City University of New York, 2013)
''This book brings together writings by feminists in the adult industry and research by feminist porn scholars. It investigates not only how feminists understand pornography, but also how feminists do porn - that is, direct, act in, produce, and consume this kind of 'industry'. With contributions by Susie Bright, Candida Royalle, Betty Dodson, Nina Hartley, Buck Angel, Lynn Comella, Jane Ward, Ariane Cruz, Kevin Heffernan, and more.''-- Fourni par l'éditeur.
Keywords: approches et analyses; arts; arts visuels et médiatiques; cinéma; communication; corps; cours; discipline; féminisme pop; féminisme pro-sexe; histoire et politique; premier cycle; ressource en ligne; sciences humaines; sex1911; sex1920; sexologie; sexualité; thématiques

Féminismes et pornographie - Courbet, David (L'attrape-corps, 2012)
Comment le féminisme peut se reconnaître dans la pornographie Objet de débats où la passion l'emporte bien souvent sur la raison, la pornographie semble à première vue s'opposer au féminisme. Or, les années 1980 voient éclore aux Etats-Unis un courant se définissant comme " pro-sexe " porté par des figures telles Annie Sprinkle ou Candida Royalle. Avec l'idée que la pornographie n'est pas systématiquement condamnable, la question suivante s'impose : peut-on parler de moyen d'émancipation ? La femme doit être libre de choisir la sexualité qui lui convient. Les films pornographiques conçus par des hommes et pour des hommes ne lui permettant pas d'obtenir une satisfaction complète, des réalisatrices, parmi lesquelles Erika Lust, Ovidie ou Emilie Jouvet, promeuvent une pornographie alternative où le plaisir féminin est - enfin - mis en exergue. Et brisent les standards pornographiques dominants ! Peu étudiées en France, les thèses défendues par les féministes pro-sexe n'ont encore que peu d'échos au sein du grand public. Basé notamment sur une dizaine d'entretiens de spécialistes et professionnels, ce travail cherche à élucider en quoi le féminisme peut se reconnaître dans la pornographie. Et inversement.
Keywords: approches et analyses; corps; cours; discipline; féminisme pop; féminisme pro-sexe; journalisme; premier cycle; science politique; science politique et droit; sciences humaines; sex1911; sexologie; sexualité; thématiques; travail

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

La chirurgie mammaire et l'esthétiquement correct : le sein et les médias - Le Louarn, S.; Le Louarn, C. (Annales de Chirurgie Plastique Esthétique, 2005)
Résumé Cet article discute en quoi les normes du sein esthétiquement correct, les caractéristiques physiologiques du sein, l'allongement de la durée de vie et les possibilités de la chirurgie esthétique influencent la demande de modification mammaire. Puis il examine comment le sujet des modifications mammaires est traité dans différents médias : presse écrite (notamment féminine), documentaires et spectacles de téléréalité. Il constate un paradoxe entre d'une part, un contexte social qui durcit des normes, encourage la quête du bien-être et la réalisation de soi et prône la tolérance et, d'autre part, la réalité d'un certain déni du droit des femmes à choisir leur apparence mammaire. L'article tente de décrypter les obstacles historiques, philosophiques, sociaux, religieux et idéologiques impliqués. Enfin, il propose une nouvelle grille de lecture du positionnement d'un individu par rapport à la chirurgie esthétique selon deux axes : le « Faire » et le « Dire ». Cette grille pourra aider le chirurgien plasticien à mieux décoder la demande de chaque patiente, pour mieux la satisfaire.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; corps féminin; cours; discipline; discours médiatique; esthétique; europe; france; féminisme pop; hétérosexisme; occident; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Feminist constructions, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis